Covid-19 and stock liquidity: evidence from top 30 Kuala Lumpur composite index - Yee Ee Chia; Ricky Chee - Jiun Chia; Mohd Ashari Bakri (Elseview, 2023)
This study examines the impact of COVID-19 and the subsequent government policy on stock liquidity traded on the top 30 companies listed on the Main Board of the FTSE Bursa Malaysia KLCI. We collect daily data for stock liquidity, the cumulative number of total cases, the cumulative number of total deaths, the number of active cases, the number of daily new cases, the total number of people vaccinated and firm-specific characteristics for the period from January 2, 2020 to June 30, 2021. The pooled ordinary least squares regression results demonstrate a negative association between COVID-19 and liquidity, suggesting that a higher proportion of COVID-19 cases deteriorate firm stock liquidity. We also document that vaccination programs assist in improving stock liquidity. Additional analysis of the industry sector shows significant differences in liquidity between sectors. The COVID-19 pandemic increases stock liquidity for the transportation and logistics sector and energy sector, but it hardly hits the plantation sector. In terms of government intervention, the vaccination program helps in improving stock liquidity for the utilities sector. Since the negative impact of COVID-19 is inevitable, future research should consider the essential role of vaccinations to recognize and forecast the behavior of stock liquidity.